Baetis (Rhodobaetis) molecularis sp. nov., a new mayfly species (Ephemeroptera: Baetidae) from the Russian Far East - Tiunova, Tatiana M.; Semenchenko, Alexander A. (Zootaxa, 2020)
A new species Baetis (Rhodobaetis) molecularis sp. nov. is described and illustrated based on larvae and reared adults from the Far East of Russia. The differential diagnosis of this species is provided with regard to other representatives of the subgenus Rhodobaetis Jacob, 2003 from East Palaearctic and Nearctic Regions. A dataset including novel and publicly available COI mtDNA sequences of 16 species of Rhodobaetis has been assembled to provide a reference dataset for DNA barcoding. The comparison between Baetis (Rhodobaetis) molecularis sp. nov. and other species produced K2P genetic distances of 0.201 in average, values well above those associated with intraspecific variation. The closest species was Baetis foemina McDonough with a K2P distance value 0.114. A Bayesian phylogeny of available Rhodobaetis is also provided.